2010
DOI: 10.4103/1319-3767.58760
|View full text |Cite
|
Sign up to set email alerts
|

Meckel′s diverticulum-Revisited

Abstract: Meckel's diverticulum is a true intestinal diverticulum that results from the failure of the vitelline duct to obliterate during the fifth week of fetal development. In about 50% cases, it contains ectopic or heterotopic tissue which can be the cause of complications. A systematic review of literature was undertaken to study the history, incidence, embryoanatomy, clinical presentation, complication and management of Meckel's diverticulum. Although Meckel's diverticulum is the most common congenital abnormality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 16 publications
0
65
0
2
Order By: Relevance
“…Resection of incidental Meckel's found during laparotomy is controversial in children and adults. It is generally recommended that asymptomatic Meckel's to be resected in children during laparotomy [2, 3] given an increased lifelong risk for complications [4]. However, this approach remains debatable in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…Resection of incidental Meckel's found during laparotomy is controversial in children and adults. It is generally recommended that asymptomatic Meckel's to be resected in children during laparotomy [2, 3] given an increased lifelong risk for complications [4]. However, this approach remains debatable in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Meckeĺs diverticulum is a true diverticulum typically located on the antimesenteric border, is the result of a failure in the obliteration of the vitelline duct (omphalomesenteric duct), which connects the yolk sac to the midgut through the umbilical cord [1], [3], [14]. MD contains all four layers of the intestinal wall with its independent blood supply [3], [10], [15].…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a diagnosis of symptomatic Meckel diverticulum is difficult preoperatively. Although symptoms can appear at all ages, clinical manifestations are more widespread in childhood (10). Higaki et al (11) examined 776 patients and concluded that diagnosis in cases that present with symptoms, with the exception of bleeding, was more difficult than in those with per-rectal bleeding.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, the diagnosis of Meckel's diverticulum is often to 6%; 40% of these complications are seen in children below the age of ten years (13) ( Table 1). The most general presentation in childhood is bleeding, which has been reported in approximately 50% of cases with symptoms related to the diverticulum (10). The most widespread complication of Meckel's diverticulum in adults is bowel obstruction, whereas this presentation occurs as the second most common complication in childhood (9,10,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation